Blinded by the whites : why race still matters in 21st-century America - Ikard, David, 1972- (Bloomington : Indiana University Press, 2013)
The scholar and author posits that the election of Barack Obama gave political currency to the (white) idea that Americans live in a post-racial society. But the persistence of racial profiling, economic inequality between Blacks and whites, disproportionate numbers of Black prisoners, and disparities in health and access to healthcare suggest there is more to the story. -- Description from dust jacket flap.
Introduction : What does Black empowerment in the twenty-first century look like? -- White supremacy under fire : the unrewarded perspective in Edward P. Jones's The Known World -- Easier said than done : making Black feminism transformative for Black men -- All joking aside : Black men, sexual assault, and displaced racial angst in Paul Beatty's The White Boy Shuffle -- Boys to men : getting personal about Black manhood, sexuality, and empowerment -- Rejecting Goldilocks : the crisis of normative white beauty for Black girls -- "Stop making the rest of us look bad" : how class matters in the attacks against the movie Precious -- Epilogue : So what does it all mean?
Includes bibliographical references (pages 165-168) and index.
Print version record.
eBooks on EBSCOhost
Keywords: American fiction -- African American authors -- History and criticism; African Americans -- Social conditions -- 21st century; African Americans in literature; Mass media and race relations -- United States; United States -- Race relations -- History -- 21st century; Roman américain -- Auteurs noirs américains -- Histoire et critique; Noirs américains -- Conditions sociales -- 21e siècle.; Noirs américains dans la littérature.; Médias et relations raciales -- États-Unis.; États-Unis -- Relations raciales -- Histoire -- 21e siècle.; LITERARY CRITICISM -- American -- General; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African Americans in literature; African Americans -- Social conditions; American fiction -- African American authors; Mass media and race relations; Race relations; United States; 2000-2099; History; Criticism, interpretation, etc